Serum and urine adropin levels following urinary microalbuminuria in patients with type 2 diabetes - Öz, Burak; Karatas, Ahmet; Uğur, Kader; Aydın, Süleyman; Gözel, Nevzat (Mümin POLAT, 2024)
ABSTRACT Objective: Diabetes mellitus disrupts energy balance due to insulin deficiency or resistance, presenting a significant public health challenge. A major complication is end-stage renal disease (ESRD), primarily resulting from diabetic nephropathy. Peptide hormones significantly contribute to the pathogenesis of diabetes. Adropin, a peptide hormone associated with energy regulation, has an unclear relationship with diabetes and nephropathy. This study aims to evaluate serum and urinary adropin levels in diabetic patients and explore the correlation between these levels and diabetic nephropathy occurrence. Materials and Methods In this cross-sectional study, serum and urine adropin levels were measured via enzyme-linked immunosorbent assay (ELISA) in 60 diabetic patients categorized by normoalbuminuria, microalbuminuria, and overt albuminuria, alongside 20 healthy controls. Results: Serum adropin levels were significantly lower in healthy controls, normoalbuminuric, and microalbuminuric groups compared to the overt albuminuric group (p=0.007, p<0.001, p=0.008). Adropin positively correlated with serum creatinine and microalbuminuria levels (p=0.031, r=0.242; p=0.001, r=0.379). Urinary adropin levels were significantly higher in diabetic patients than in controls (p=0.001) and lower in the microalbuminuric group compared to both normoalbuminuric and overt albuminuric groups (p=0.026 for both). Conclusion: Adropin levels are significantly altered in diabetic nephropathy, highlighting its potential as both a biomarker and a therapeutic target due to its involvement in insulin sensitivity, inflammation, and metabolic pathways. Future research should investigate the mechanisms through which adropin influences renal function and its therapeutic potential in metabolic disorders, especially in diabetic kidney disease, while also addressing the implications of adropin resistance.
Keywords: Medical Biochemistry - Proteins; Peptides and Proteomics; Tıbbi biyokimya - Proteinler; Peptitler ve Proteomik